O pewnych walorach nie-dietetycznej ontologii: wyznanie nawróconego anty-ingardenisty - Jadacki, Jacek (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2009)
The main impulse for this considerations is a beautiful Professor Adam Nowaczyk's text "Thespell of Plato. Reflections on Roman Ingarden's ontology".My general (negative) thesis is that no hyper-dietetic, i.e. monocategorial, ontology (meantas the theory of real objects) is not correct. Thus neither the theory of sets (if it assumed theuniqueness of the ontic category of sets), nor reism (if it assumed the uniquenes of the onticcategory of things) or eventism (if it assumed the uniqueness of the ontic category of events) arecorrect ontologies (meant as theses on existence of a certain ontic category).The consequence of this negative thesis is that only non-dietetic, i.e. polycategorial, ontologycan be correct.I present a few arguments on account of theses two theses.